ASSET MANAGEMENT FOR COMMUNITY ECONOMIC SUSTAINABILITY IN VILLAGE-OWNED ENTERPRISES (BUMDES) JAYA JANTI, KLATEN REGENCY: Pengelolaan Aset untuk Keberlangsungan Ekonomi Masyarakat di Badan Usaha Milik Desa (BUMDes) Jaya Janti Kabupaten Klaten - Ismawati Septiningsih; Itok Dwi Kurniawan; Bambang Santoso; Muhammad Rustamaji; Arsyad Aldyan (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
BUMDes Janti Jaya is a village-owned business entity located in Janti Village, Polanharjo District, Klaten Regency. If supervised and managed properly, all profits generated by BUMDES Janti Jaya can have a significant impact on the welfare of the community in Janti Village. However, in reality, the management of BUMDes in Janti Village has not met the basis of the principles of BUMDes management, namely the lack of participatory attitude from the community. In order to improve the management of BUMDes Jaya Janti, especially in terms of asset management, the Service Team held socialization related to this. This service activity was carried out by the lecture method to provide knowledge to the community about the urgency of BUMDes in the economic growth of the community. As a result, the implementation of service by lecturers at the Faculty of Law, Universitas Sebelas Maret (UNS) has had a significant positive impact on the management and preparation of BUMDes financial statements.